CD49f Acts as an Inflammation Sensor to Regulate Differentiation, Adhesion, and Migration of Human Mesenchymal Stem Cells. (23rd June 2015) - Yang, Zhigang; Dong, Ping; Fu, Xin; Li, Qiuchen; Ma, Shize; Wu, Dongying; Kang, Ning; Liu, Xia; Yan, Li; Xiao, Ran
Abstract The advent of mesenchymal stem cell (MSC)‐based therapies has been an exciting innovation for the treatment of degenerative and inflammatory diseases. However, the surface markers that accurately reflect the self‐renewal and differentiation potential of MSCs and their sensitivity to environmental cues remain poorly defined. Here, we studied the role of CD49f in bone marrow MSCs (BMSCs) and the mechanism by which it regulates the behavior of BMSCs under inflammatory conditions. We found that CD49f is preferentially expressed in fetal cells rather than adult cells, CD49f‐positive BMSCs possess higher CFU‐F formation ability and differentiation potential than CD49f negative cells, and the CD49f expression of BMSCs gradually decreases during in vitro passaging. CD49f knockdown dramatically decreased the differentiation of BMSCs and isoform A was demonstrated to be the main functional form that enhanced the differentiation ability of BMSCs. The influences of inflammatory cytokines on BMSCs revealed that TNF‐α downregulated CD49f in BMSCs with impaired differentiation, decreased adhesion to laminins, and increased migration. Moreover, tissue transglutaminase was found to work together with CD49f to regulate the behavior of BMSCs. Finally, we showed that mTOR signaling rather than NF‐κB activation mediated CD49f downregulation induced by TNF‐α and maintained CD49f homeostasis in BMSCs. Our findings suggest that CD49f is a stemness marker of BMSCs and is tightly correlated with the behavioral changes of BMSCs under inflammatory conditions. These data demonstrate a novel role for CD49f in sensing inflammation through mTOR pathway to further modulate the behavior of MSCs to fulfill the requirements of the body. Stem Cells2015;33:2798—2810